EFFECT OF GIVING ANTIHYPERTENSIVE DRUG AGAINST REDUCTION OF BLOOD PRESSURE IN ACUTE ISCHEMIC STROKE PATIENTS WHO HOSPITALIZED IN RSUP DR. SARDJITO YOGYAKARTA - Wahyu Sedjatiningsih; Zullies Ikawati; Abdul Gofir (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Incidence of ischemic stroke 10 times more often than haemorrhagic stroke in the the west countries, but haemorrhagic stroke has a higher risk of mortality than ischemic stroke. One focus of acute stroke management is the management of hypertension. Blood pressure reduction in ischemic stroke patients could potentially reduce the risk of brain edema, the risk of hemorrhage, and prevent further vascular damage. However, an aggressive blood pressure reduction can cause a decrease in perfusion pressure to the ischemic area. Most hypertensive patients require two or more antihypertensive medications to achieve blood pressure targets. This study used observational study design with retrospective data collection on medical records of acute ischemic stroke patients and performed in RSUP Dr. Sardjito Yogyakarta period January 2010-December 2010. Data were analyzed with descriptive analysis and chi-square evaluative analysis on the relationship between the type of therapy with a reduction in blood pressure of acute ischemic stroke patients. Initial antihypertensive medication use in patients with acute ischemic stroke in RSUP Dr. Sardjito were 13 types of five classes of antihypertensive drugs. After getting a single antihypertensive medication, patients who experienced a decrease in systolic blood pressure on day-3 was 60%, while 17% fixed and 23% up and after getting a combination of antihypertensive medications, patients who experienced a decrease in systolic blood pressure on day-3 was 75%, while 10% fixed and 15% rise. Antihypertensive drug therapy alone or in combination had the same ability to lower systolic blood pressure (p = 0.260) and diastolic (p = 0.567) in patients with acute ischemic stroke in RSUP Dr. Sardjito Yogyakarta. Keywords: Hypertension, acute ischemic stroke, single antihypertensive drug, antihypertensive drug combinations, RSUP Dr.Sardjito Yogyakarta